Presence of decoy cells for 6 months on urine cytology efficiently predicts BK virus nephropathy in renal transplant recipients. (1st September 2021) - Sekito, Takanori; Araki, Motoo; Yoshinaga, Kasumi; Maruyama, Yuki; Sadahira, Takuya; Nishimura, Shingo; Wada, Koichiro; Watanabe, Masami; Watanabe, Toyohiko; Tanabe, Katsuyuki; Takeuchi, Hidemi; Morinaga, Hiroshi; et al.
Abstract : Objectives: To investigate the association between duration of consecutive presence of decoy cells on urine cytology and BK virus nephropathy after kidney transplantation. Methods: In total, 121 kidney transplant recipients were retrospectively evaluated. The best duration of consecutive presence of decoy cells that could be used to predict BK virus nephropathy was analyzed using the area under the curve for each duration, and recipients were divided into two groups based on the best predictive performance. The effectiveness of SV40 immunostaining on urinary cytology was also analyzed. Results: In total, 2534 urine specimens as well as SV40 immunostaining in 2241 urine specimens were analyzed. Six consecutive months of decoy cell positivity had the best predictive performance for BK virus nephropathy (area under the curve = 0.832). The incidence of BK virus nephropathy in recipients with positive decoy cells for 6 months or more consecutive months (5/44) was significantly higher than in those who had positive decoy cells for less than 6 months (0/77; P = 0.005). Decoy cell positivity had a sensitivity, specificity, positive predictive value, and negative predictive value for BK virus nephropathy of 100%, 66%, 11%, and 100% respectively. SV40 immunostaining provided slightly better specificity (68%) and positive predictive value (12%). Conclusions: The detection of decoy cells at 6 months or more on urine cytology had high predictive value for BK virus nephropathy in kidney transplant recipients. SV40 immunostaining on urine cytology added minimal diagnostic accuracy.